2015
DOI: 10.1111/asj.12424
|View full text |Cite
|
Sign up to set email alerts
|

Oral antibiotics enhance antibody responses to keyhole limpet hemocyanin in orally but not muscularly immunized chickens

Abstract: Recent studies have emphasized the crucial role of gut microbiota in triggering and modulating immune response. We aimed to determine whether the modification of gut microbiota by oral co-administration of two antibiotics, ampicillin and neomycin, would lead to changes in the antibody response to antigens in chickens. Neonatal chickens were given or not given ampicillin and neomycin (0.25 and 0.5 g/L, respectively) in drinking water. At 2 weeks of age, the chicks were muscularly or orally immunized with antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Keyhole limpet hemocyanin (KLH) is a high-molecularweight copper-containing protein found in the hemolymph of the marine mollusk Megathura crenulata (80). This extracellular respiratory protein has many bioactive properties (81)(82)(83), including immunostimulatory, antitumor, and antimicrobial activity. Riggs et al and McFadden et al (84,85) have shown that KLh from the giant keyhole limpet significantly inhibits the growth of different cancer cells in vitro, including estrogendependent breast cancer cells (MCF-7), estrogen-independent breast cancer cells (ZR75-1), pancreatic cancer cells (PANC-1), prostate cancer cells (DU145), and Barrett's esophageal adenocarcinoma cells (SEG-1 and BIC-1).…”
Section: Shrimp Wilson-sanchez Et Almentioning
confidence: 99%
“…Keyhole limpet hemocyanin (KLH) is a high-molecularweight copper-containing protein found in the hemolymph of the marine mollusk Megathura crenulata (80). This extracellular respiratory protein has many bioactive properties (81)(82)(83), including immunostimulatory, antitumor, and antimicrobial activity. Riggs et al and McFadden et al (84,85) have shown that KLh from the giant keyhole limpet significantly inhibits the growth of different cancer cells in vitro, including estrogendependent breast cancer cells (MCF-7), estrogen-independent breast cancer cells (ZR75-1), pancreatic cancer cells (PANC-1), prostate cancer cells (DU145), and Barrett's esophageal adenocarcinoma cells (SEG-1 and BIC-1).…”
Section: Shrimp Wilson-sanchez Et Almentioning
confidence: 99%
“…Changes in gut microbiome caused by antibiotics have been shown to impact antibody responses 17–20 . We therefore additionally checked whether the continuous exposure of mice to antibiotic treatment had any significant impact on antigen‐specific IgE and IgG1 levels during the primary, memory, and secondary infection phase in SPF and Abx mice.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in gut microbiome caused by antibiotics have been shown to impact antibody responses. [17][18][19][20] We therefore additionally checked whether the continuous exposure of mice to antibiotic treatment had any significant impact on antigen-specific IgE and IgG1 levels during the primary, memory, and secondary infection phase in SPF and Abx mice. Overall, we observed that HES-specific IgE and IgG1 levels were similar in both SPF and antibiotic treated mice in primary and secondary infections (Figure 4A,B).…”
Section: Spf and Abx Mice Show Similar Parasitespecific Ige And Igg1 ...mentioning
confidence: 99%
“…Therefore, many studies investigate how the use of antibiotics during the first weeks, post-hatch, affects the response in specific antibodies at later stages of the chickens' life. Antigenic keyhole limpet hemocyanin (KLH) oral immunisation of two-week-old chicks receiving orally ampicillin and neomycin increased the production of antibody response (IgM, IgA, and IgY) two-or threefold compared to the control group, and the count of Lactobacillus in the chickens' feces decreased (Murai et al, 2016). The use of antibiotics temporarily disturbs the microbiological balance, and decreases the diversity and abundance of micro-organisms in the gastrointestinal tract.…”
Section: Antibioticsmentioning
confidence: 99%